2018
DOI: 10.1038/s41467-018-05068-w
|View full text |Cite
|
Sign up to set email alerts
|

An in vitro paradigm to assess potential anti-Aβ antibodies for Alzheimer’s disease

Abstract: Although the amyloid β-protein (Aβ) is believed to play an initiating role in Alzheimer’s disease (AD), the molecular characteristics of the key pathogenic Aβ forms are not well understood. As a result, it has proved difficult to identify optimal agents that target disease-relevant forms of Aβ. Here, we combined the use of Aβ-rich aqueous extracts of brain samples from AD patients as a source of human Aβ and live-cell imaging of iPSC-derived human neurons to develop a bioassay capable of quantifying the relati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
65
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 54 publications
(70 citation statements)
references
References 70 publications
5
65
0
Order By: Relevance
“…Recent evidence suggests that only a fraction of Aβ oligomers in AD brain tissue are neurotoxic 21,24 and that these toxic oAβ species are not equally targeted by different anti-oAβ monoclonal antibodies. 15 The consistent and significant decreases in rigorously measured oAβ we describe here indicate that crenezumab at doses of up to 15mg/kg IV is engaging in vivo with its planned target, cerebral oAβ; ongoing studies of crenezumab, testing a 4-fold higher dose (60mg/kg IV) in presymptomatic familial AD subjects, could determine whether the degree of decrease in oAβ corresponds to the attenuation of cognitive decline. Similarly, it will be important to further assess how CSF oAβ levels change over the course of the disease, and whether the sensitive measurement of oAβ as performed here could aid in the diagnosis of early stage AD.…”
supporting
confidence: 55%
See 1 more Smart Citation
“…Recent evidence suggests that only a fraction of Aβ oligomers in AD brain tissue are neurotoxic 21,24 and that these toxic oAβ species are not equally targeted by different anti-oAβ monoclonal antibodies. 15 The consistent and significant decreases in rigorously measured oAβ we describe here indicate that crenezumab at doses of up to 15mg/kg IV is engaging in vivo with its planned target, cerebral oAβ; ongoing studies of crenezumab, testing a 4-fold higher dose (60mg/kg IV) in presymptomatic familial AD subjects, could determine whether the degree of decrease in oAβ corresponds to the attenuation of cognitive decline. Similarly, it will be important to further assess how CSF oAβ levels change over the course of the disease, and whether the sensitive measurement of oAβ as performed here could aid in the diagnosis of early stage AD.…”
supporting
confidence: 55%
“…1C22, used as the capture antibody, is a strongly Aβ aggregate-preferring mouse mAb developed in the Walsh laboratory and described previously. 14,15 3D6, used as the detector antibody, is a mouse mAb specific for the Asp1-containing N-terminus of Aβ 16,17 and was from the hybridoma PTA5130 (ATCC, Manassas, VA). 1C22 was biotinylated using an SMC Capture Labeling Kit (Millipore), and the biotinylated 1C22 was allowed to bind to Dynabeads Myone Streptavidin C1 microparticles (MPs; Life Technologies, Eugene, OR) to yield 12.5μg of biotinylated 1C22 per milligram of MPs.…”
Section: Methodsmentioning
confidence: 99%
“…Hence, rather than relying on simple binding assays to understand and target the small portion of Aβ that is toxic, it is essential to utilize bioactivity assays. To address whether PrP-grafted mAbs recognize toxic Aβ we utilized a very recently developed medium-throughput video-microscopy paradigm to monitor disruption of neurite integrity by AD brain derived Aβ Jin et al, 2018). In prior studies we demonstrated that certain anti-Aβ mAbs could attenuate AD brain Aβ mediated neuritotoxicity .…”
Section: Discussionmentioning
confidence: 99%
“…Having established that PrP-motif grafted antibodies can bind aggregated Aβ in AD brain extracts, we next assessed whether these mAbs recognize bioactive Aβ species. Recently, we described a live-cell imaging paradigm to measure the effect of AD brain extracts on human neurons Jin et al, 2018). Differentiated iPSC-derived human neurons (iNs) (see Figure 3A and 3B for a details) were treated with AD brain extracts and imaged every two hours for 72 hours.…”
Section: Prp and Prp N1 But Not Prp-grafted Antibodies Protect Againmentioning
confidence: 99%
“…64 Calcium oscillations can be monitored to show network formation through automated and noninvasive imaging in 96-or 384-well plates. [168][169][170][171] Calcium imaging has been performed in either intact or dissociated cerebral organoids to demonstrate that spontaneous surges of intracellular calcium correspond to electrical activity. 25,28,32 In addition, in vivo two-photo calcium imaging systems can be applied for longitudinally measuring neuronal network activities of grafted organoids in rodent brain.…”
Section: Assays For Measuring Hpsc-derived Neuronal Activity and DImentioning
confidence: 99%